2021
DOI: 10.5114/aoms/110672
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine expression in patients with ovarian cancer or benign ovarian tumors

Abstract: IntroductionChemokines play a crucial role in tumor growth and progression according to proangiogenic and immunosuppressive acting. This study was aimed to investigate the serum levels of selected chemokines in patients with ovarian cancer or benign ovarian tumors to point on their role in tumorigenesis and their potential use in preoperative diagnosing of adnexal mass.Material and methodsThe study group consisted of 59 women with ovarian cancer: 17 epithelial ovarian cancer (EOC) patients and 42 women with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Differences in chemokine concentrations in the blood plasma of humans were shown by some authors. Nowak et al analyzed chemokines CX3CL1 and CXCL12 in the blood of patients with ovarian cancer or benign ovarian tumors [ 58 ]. CX3CL1 was detected at 5–15 pg/mL, while CXCL12 was detected at 800–1000 pg/mL, coinciding with the inducible and homeostatic chemokines, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in chemokine concentrations in the blood plasma of humans were shown by some authors. Nowak et al analyzed chemokines CX3CL1 and CXCL12 in the blood of patients with ovarian cancer or benign ovarian tumors [ 58 ]. CX3CL1 was detected at 5–15 pg/mL, while CXCL12 was detected at 800–1000 pg/mL, coinciding with the inducible and homeostatic chemokines, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, biological evidence suggests that inflammation is a hallmark of cancer(Greten and Grivennikov, 2019). Some studies have suggested that the chemokines and cytokines released by cancer and stromal cells are mediators of inflammation(Nowak et al, 2022). The activationP r e p r i n tof inflammatory cytokines can lead to cancer, including OC(Bouras et al, 2022).…”
mentioning
confidence: 99%